Evaluation of Malt Barley (Hordeum distichon L.) Varieties for Yield and Agronomic Traits in South Gondar, Ethiopia - Tiringo Yilak Alemayehu; A. Momina (International Journal of Agronomy)
The production and productivity of malt barley are limited using disease-susceptible and low-yielding varieties. Study was focused on identifying and selecting the best performed and adapted malt barley variety/varieties for yield and yield-related traits. We evaluated six improved malt barley varieties using a randomized complete block design with three replications. The study was conducted for 2 years (2019 and 2020 cropping season) at Lay Gayint district. The combined analysis showed highly significant differences (P<0.01) among varieties, years, and their interactions in all traits. The highest yield (31.54 qt·ha−1) was obtained from variety Holker. The correlation coefficient analysis showed a significant and very strong positive association of grain yield with number of effective tillers (r=0.953∗∗), spike length (r=0.973∗∗), and strong positive association with thousand seed weight (r=0.739∗∗) with a medium positive association with seed per spike (0.554∗∗). In principal component analysis, PC1 was dominated by traits that had a greater effect on yield. A variety of Holker could be recommended in the study areas and other similar agro-ecologies. Farmers lost a lot of quintals of yield by lack of new technologies, by addressing more adapted improved production technology increased average yield.